La variació social - Boix, Emili (Caplletra. Revista Internacional de Filologia, 1998)
First, this paper describes the relations between stratification and social convencionalization in general, it also presents a view of society as a very appropiate ground for socilectal research. Second, after reviewing specific problems of the research mentioned above in the Catalan countries, four lines of related research are surveyed: (1) dialectal and phonological research (2) sociological research (3) literary and mass media research (4) prescriptive and lexicographic research Some aspects of sociolinguistic research are especially reviewed: the repertoire in Barcelona and some of their sociolects as it is the case of the ’xava.’